The effects of short versus long inter-set rest intervals in resistance training on measures of muscle hypertrophy: A systematic review - Grgic, J.; Lazinica, B.; Mikulic, P.; Krieger, J. W.; Schoenfeld, B. J. (European Journal of Sport Science, 2017)
Although the effects of short versus long inter-set rest intervals in resistance training on measures of muscle hypertrophy have been investigated in several studies, the findings are equivocal and the practical implications remain unclear. In an attempt to provide clarity on the topic, we performed a systematic literature search of PubMed/MEDLINE, Scopus, Web of Science, Cochrane Library, and Physiotherapy Evidence Database (PEDro) electronic databases. Six studies were found to have met the inclusion criteria: (a) an experimental trial published in an English-language peer-reviewed journal; (b) the study compared the use of short (=60 s) to long (>60 s) inter-set rest intervals in a traditional dynamic resistance exercise using both concentric and eccentric muscle actions, with the only difference in resistance training among groups being the inter-set rest interval duration; (c) at least one method of measuring changes in muscle mass was used in the study; (d) the study lasted for a minimum of four weeks, employed a training frequency of =2 resistance training days per week, and (e) used human participants without known chronic disease or injury. Current evidence indicates that both short and long inter-set rest intervals may be useful when training for achieving gains in muscle hypertrophy. Novel findings involving trained participants using measures sensitive to detect changes in muscle hypertrophy suggest a possible advantage for the use of long rest intervals to elicit hypertrophic effects. However, due to the paucity of studies with similar designs, further research is needed to provide a clear differentiation between these two approaches.